Prevention of STD/ Aids: an approach close to adolescents families - Fernandes, Ana Fatima Carvalho; Gurgel, Almerinda Holanda; Julião, Thereza Cristina (Brazilian Journal of Sexually Transmitted Diseases, 2022)
This study has as objective knows the preparation of the families and your performance in the prevention of STD/Aids in the youths. lt is a study of nature exploratory, descriptive, with qualitative approach. The data were collected with 15 families originating from of the municipal district of Redenção Ceará, in the period of January to February of 1999, analyzed in agreement with the methodology proposed by Bardin ( 1977) and it allowed the construction of the follo-wing ones thematic: Knowledge on STD/Aids, Performance of the Family and Changing Directions. It was verified that the families use the dialogue with advertisement in the youths’ education for the prevention, however it dashes in barriers as: p rejudices, taboos, shame, the youths’ easiness with the personal risk and lack of time of the country. It was ended that the families don’t have enough knowledge on STD/Aids, and they don’t participate in an efficient way in the prevention of these diseases, hindering like this the adolescents education.